Temporärer Bauchdeckenverschluss bei Laparostoma - Wolff, Stefanie; Haupt, Werner; Croner, R. (Chirurgische Praxis, 2019)
Laparostomy is used in the treatment of abdominal compartment syndrome, abdominal trauma and severe persisting peritonitis. Since the open abdomen can lead to major surgical complications, the closure of the abdominal fascia should be achieved as soon as possible. Often a temporary closure technique has to be applied prior to definitive abdominal closure. Currently, the vacuum-assisted closure therapy is recommended for temporary abdominal closure. However, contraindication should be considered. Patients who are treated with open abdomen show an increased risk of ventral hernia and intestinal fistulas as well as an elevated mortality rate of 30 %.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Abdominal compartment syndrome; Open abdomen; Temporary abdominal closure